Caracterização química e física do cajueiro (Anacardium occidentale L.) - Dantas, Fernanda Cinthia Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
The aim of this study was the physical and chemical characterization of the Anacardium occidentale L. (Cashew tree) wood. To perform tests at the Wood Technology Laboratory of UFERSA, ten trees were collected from crops located at the coast of Ceará. Samples with 2,5 x 2,5 x 3 cm dimensions (transversal and longitudinal, respectively) were produced to evaluate the physical properties (bulk and basic density, linear and volumetric contractions and anisotropic factor). All procedures were based on the Brazilian standard NBR 7190 (1997). For elemental and immediate chemical analysis, five individuals were collected and from each one three discs from different tree heights were produced. Bark from all samples were pilled off and saved as only one batch. There was no significant statistic difference for the immediate chemical analysis from different diametric classes, with exception of extractive content. Bark presented statistically different values for all evaluated variables when compared with wood. Average bulk and Basic density were 0,51g/m³ e 0,43g/m³. Cashew wood was then considered as low to medium density wood. There was no statistically difference for maximum volumetric contraction, tangential contraction, maximum volumetric swelling and anisotropic factor between sapwood and heartwood. The difference was observed only for radial contraction. Average anisotropic factor was 1,38 and values of radial, tangential and volumetric contraction were considered low. Those results indicated that cashew wood has a good dimensional stability.
Monografia
Keywords: Densidade; Anisotropia; Alburno; Cerne; Density; Anisotropy; Sapwood; Heartwood; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL